The Changes in Young Households' Tenure Choice across Time: Evidence from American Housing Survey. - Zhou, Yanting. (2017)
Abstract: Despite the overall increase in the homeownership rate across decades, the U.S. housing market has seen a decrease among young households. This paper takes into account the investment value and consumption cost of a housing unit, as well as education, income, and other demographic factors to study the tenure choice process of young households. The study also adopts the Oaxaca Decomposition to decompose the difference in homeownership rate between time periods into coefficients and endowments effects to understand the real source of these changes.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Economics.; Advisor: Jeffrey Zabel.; Committee: Anna Hardman.; Keyword: Economics.